2007
DOI: 10.1111/j.1468-3083.2007.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and coping strategies in patients with psoriasis: the PSYCHAE Study

Abstract: (i) Psychological distress was relatively frequent in our patients with psoriasis; (ii) female gender was the most important predictive factor for psychological distress; (iii) there was no association between psoriasis severity and psychological distress; (iv) planning and active coping were the coping strategies most frequently employed by patients; and (v) most dermatologists employed a problem-orientated attitude in caring for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
84
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 52 publications
21
84
1
1
Order By: Relevance
“…Presence of psoriatic arthritis, psychiatric disorders, and other co-morbidities may further worsen QoL and should be taken into account. The association between symptom severity and QoL, though observed by some studies [98,116], is not always strong, and other studies found no significant association at all [48,95]. Symptom severity has been shown to have a greater direct impact on the physical rather than the mental components of QoL, while the effects of stigmatization on QoL are more strongly mental [67].…”
Section: Conclusion and Recommendations For Clinical Practicementioning
confidence: 85%
See 3 more Smart Citations
“…Presence of psoriatic arthritis, psychiatric disorders, and other co-morbidities may further worsen QoL and should be taken into account. The association between symptom severity and QoL, though observed by some studies [98,116], is not always strong, and other studies found no significant association at all [48,95]. Symptom severity has been shown to have a greater direct impact on the physical rather than the mental components of QoL, while the effects of stigmatization on QoL are more strongly mental [67].…”
Section: Conclusion and Recommendations For Clinical Practicementioning
confidence: 85%
“…The same authors investigated patients' coping strategies and found that planning, active coping and acceptance were strategies most commonly employed by their patients while denial, behavioural disengagement, and substance abuse were the least frequent attitudes [48]. During the 12-month follow-up, active coping and avoiding dramatization by recourse to humor were predictive factors of amelioration of PD [66].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological distress is common in psoriatic patients (Colombo et al, 2010c;Finzi et al, 2007). A large, observational, follow-up study of more than 1500 psoriatic patients (the PSYCHAE study) revealed that methotrexate and topical corticosteroids were associated with a significantly increased risk of minor psychological distress, whereas cyclosporin significantly reduced such distress, perhaps because of patients' overall perceptions of efficacy and tolerability (Colombo et al, 2010c).…”
Section: Clinical Efficacymentioning
confidence: 99%